Deskripsi Karakter Disiplin Dan Kerja Keras Pada FilmKarate Kid (Analisis Isi Cerita Film KARATE KID untuk media pembelajaran PPKn) - , Zulfikar; ZULFIKAR, Drs. Yulianto Bambang Setyadi, M. Si (2016)
This study aimed to describe the character of discipline and hard work on the film Karate Kid (analysis of the content of the film Karate Kid for instructional media PPKn). This type of research is qualitative descriptive. This research subject is the movie Karate Kid. The object of this study is the character of discipline and hard work on the movie Karate Kid. Data collection techniques in this study using documentation and literature study. Test the validity of the data by triangulation triangulation of data sources and data collection techniques. The data analysis applying the models of content analysis through finding emblem/symbol, a classification based on the emblem/symbol, prediction/ analyzing data.The results of this study can be concluded that: 1) The character of the discipline can be found in the character Dre Parker in the movie Karate Kid, namely: a) Always order to perform well at a specified time, b) Conduct in the spoken language, c) Obedient in run the command; 2) The character of hard work can be found in the character Dre Parker in the movie Karate Kid, namely a) the desire and unyielding, b) have a high morale, c) trying in earnest; 3) The character of discipline in character Dre Parker in the movie Karate Kid basic competencies contained in Pancasila and Citizenship Education Class VII SMP, namely: 2.3. Respect and appreciate the honest behavior, discipline and responsibility, caring (tolerance, mutual assistance), mannered, confident in interacting effectively with the social and natural environment within reach of the association and its existence. Character hard work is contained in the book Pancasila and Citizenship Education Junior Class VII in the Basic Competence Cultivating Awareness and Attachment to Norma. Characters discipline and work can be found in the character Dre Parker in the movie Karate Kid which can be exemplified by learners are obedient in running order, always orderly duty at the appointed time, never give up, morale is high, and strive earnestly